Propuesta De Un Modelo De Control Interno Efectivo Para Optimizar La Gestión Administrativa De Las Cooperativas De Ahorro Y Crédito De La Ciudad De Loja. - Palacios Jiménez, Fernanda Elizabeth (2016)
The present investigation work you developed previous the obtaining of the title of Engenders in Accounting and Audit in the National University and Loja outlined as objectives the following ones to Elaborate a model of control internal cash for the saving cooperatives and credit from the one to City of Loja that allows to optimize the administration so much administrative as financial; To contribute with this model to diminish the financial and operational risks, to provide dependability to the execution of norms, laws and political, to promote an appropriate control culture and to strengthen the operations that are given in this entities. For the development of this investigation a design was used that allowed and installation of the pattern of effective internal control; the same part of l an I Diagnose situational of the control in the Cooperatives of Saving and Credit stops then to propose a model of Internal control that allows the appropriate taking of decisions based on the norms of internal control, for the financial sector of the country, The results of the carried out work are synthesized in the following way the designed pattern it is guided to the saving cooperatives and credit registered in the National Address of Cooperative and that they are forced to constantly improve in their operations, when applying an effective internal control you is in a continuous improvement, what will generate services of better quality, competitive, recognition and positioning in the cooperative and financial sector at national level. The globalization in the country, the seizure of foreign capital in the national banking has forced to the saving cooperatives and credit to improve its administrative process for what you/they will be obtained when accepting and to implement the Pattern of Effective Internal Control in the administrative administration favorable changes, among those that are mentioned: A cooperatives culture will be fomented, through the of the whole personnel for the achievement of the objectives of the cooperative. He implements of the Internal Control it will minimize the sub-use of the resources of the cooperative. To redefine and/or to improve political in the administrative administration and in the financial administration. An effective communication will be achieved that promulgates the different internal and external politicians for the achievement of the general objectives, a better communication toward inside and toward outside of the cooperative. It will facilitate the taking decisions related in the improvement of products, service to the partners, the strengths and weaknesses of the competition, the financial position, the organization, the technology, the personal one and therefore to the correct definition of strategies that you/they collaborate to the achievement of the objectives of the cooperatives. The proposal of the Pattern of Control Internal Cash understands four stages: Stage I: Situational analysis FODA. ; Stage II: Effective Internal control; Stage III: Evaluation of Results and Actions; Stage IV: Plan of Implementation. Situational analysis FODA in this stage the internal and external variables will be investigated to discover critical situations and to identify possible risks he/she stops then to obtain a diagnosis on the current situation of the cooperative. Effective Internal control (C.I.E.) he/she Understands the tools that will be used to evaluate in way specific las4 workspaces: administrative, financial, operative and legal; those which in turn have been subdivided in work units. Evaluation of Results and Actions. The advice receives and it evaluates the report of results or discoveries of the previous stage, they take decisions on the actions of improvement and then you pursuit to the same ones. Plan of Implementation Understands the action plan, in which intends how the proposal, the chronogram of activities will be developed to develop in a period of certain time and the budget that it is the summary in monetary terms that he/she will make the cooperative. Among the main conclusions we have that In the saving cooperatives and credit of the city of Loja, an appropriate Effective Internal Control of its countable and financial administrative operations doesn't exist, what has become a problem for the directive. The saving Cooperatives and credit don't have defined an organizational structure that allows them an effective relationship among the different sections or department that conform it. The countable structure is not the most appropriate; many not even have a countable system that registers its daily operations and show at the end of an exercise the results. The processes of control of the administrative, financial, computer areas, operations and legal, they don't contribute to the efficiency and effectiveness in the execution of goals and objectives. For what is recommended; the directive and managers of these saving cooperatives and credit should improve the systems of Effective Internal Control of their resources, what will contribute to the obtaining of good results of the operations that you/they develop. therefore the application of the minimum administrative structure is recommended designed in this investigation, with that which will be obtained an appropriate control of the human resources, materials and financiers. The immediate application of the countable, administrative, operative and legal infrastructure, that which will allow to know the economic and financial results of one period. The proposal contains a model series of effective Internal Control for the main departments, what will contribute to improve the countable and financial handling of the cooperatives of saving and Credit of the city of Loja